Prospect of Good Governance and Human Development - Chaudhary, Deepak (Nepalese Journal of Development and Rural Studies, 2019)
The governance now became a buzzword in political economy. It contributes to accelerating the overall development including human development and its role in making effective delivery of social and public services are crucial. This paper analyzes the relationship between governance and human development based on published data, document and theories. The concept of governance and human development emerged after 1980. The proper function of governance in terms of political, economic and administrative can create sound development. Rule of Law, participation, public accountability and responsiveness, transparency, equity and inclusion, efficiency, and decentralization are a key institutional framework for democratic or good governance. These principles are structured to performing well for the assigned goals and objectives, transparent decisions, focusing on the organization’s purpose and outcomes, capacity building, and managing and mitigating risks factors. If there is enough authority, capacity, economic resource, and good governance, human development can easily be achieved. Therefore, the linkage between governance and human development is inevitable.